Effects of Liqi Tongbian decoction on gut microbiota, SCFAs production, and 5-HT pathway in STC rats with Qi Stagnation Pattern - Liu, Qihong; Ke, Danfeng; Chen, Youqin; Shen, Aling; Liu, Liya; Hu, Lunan; Ren, Yan; Fang, Wenyi; Zhao, Peilin; Sferraf, Thomas J.; Luo, Yunfeng; Ke, Xiao (Frontiers in Microbiology, 2024)
Slow Transit Constipation (STC) is a common and debilitating condition characterized by delayed colonic transit and difficulty in fecal expulsion, significantly impacting patients' physical and mental well-being as well as their overall quality of life. This study investigates the therapeutic potential of Liqi Tongbian Decoction (LTD) in the treatment of STC, especially in cases involving the context of Qi stagnation through a multifaceted approach involving the modulation of intestinal flora and shortchain fatty acids (SCFAs). We employed a rat model of STC with Qi stagnation, established using a "loperamide + tail-clamping provocation method," to explore the effects of LTD on fecal characteristics, intestinal motility, and colonic pathology. Importantly, LTD exhibited the ability to increase the richness, diversity, and homogeneity of intestinal flora while also modulating the the composition of microorganisms. It significantly increased the production of SCFAs, especially in butyric acid. Moreover, LTD exerted a substantial influence on the synthesis of serotonin (5-HT) by modulating the expression of tryptophan hydroxylase (TPH) and interacting with the 5-HT4 receptor(5-HT4R), resulting in enhanced colonic motility. Correlation analyses revealed a positive correlation between certain bacterial genera, such as Lachnospiraceae_NK4A136 spp. and Clostridium spp., and the concentrations of butyric acid and 5-HT. These results suggest a mechanistic link between microbiome composition, SCFA production, and 5-HT synthesis. These findings highlight the potential of LTD in alleviating STC by facilitating a beneficial interplay among intestinal flora, SCFAs production, and 5-HT-mediated colonic motility, providing novel insights into the management of STC with Qi stagnation.